Cluster randomised control trial for cricket injury prevention programme (CIPP): a protocol paper. Issue 3 (28th September 2017) - Soomro, Najeebullah; Chua, Nina; Freeston, Jonathan; Ferdinands, Rene E D; Sanders, Ross
Abstract : Background: Injury prevention programmes (IPPs) are effective in reducing injuries among adolescent team sports. However, there is no validated cricket-specific IPP despite the high incidence of musculoskeletal injuries among amateur cricketers. Objectives: To evaluate whether a cricket injury prevention programme (CIPP) as a pretraining warm-up or post-training cool-down can reduce injury rates in amateur cricket players. Methods: CIPP is a cluster randomised controlled trial which includes 36 male amateur club teams having cricket players aged 14–40 years to be randomly assigned to three study arms: warm-up, cool-down and control (n=12 teams, 136 players in each arm). The intervention groups will perform 15 min CIPP either as a pretraining warm-up or a post-training cool-down. Outcome measures: The primary outcome measure will be injury incidence per 1000 player hours and the secondary outcome measures will be whether IPP as a warm-up is better than IPP as a cool-down, and the adherence to the intervention. Trial registration number: ACTRN 1261700047039.